(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Coronary heart disease and cerebrovascular disease are the two main contributors of global morbidly and mortality. Coronary Heart Disease deaths in Bangladesh reached 1,63,769 or 17.11% of total deaths and reaches 25th in world. Importantly quality of life among them can modify the coronary heart disease. The opportunity for improved quality of life should be a factor in the health care provider’s decision to recommend the treatment procedure. Objective: To ascertain the physical and mental health component of Quality of Life with sociodemographic characteristics and health-related morbidity status among admitted coronary heart disease patients. Materials and Methods: This cross-sectional study was conducted from January 2013 to December 2013 among coronary heart disease patients admitted in Cardiology department of Combined Military Hospital, Dhaka. The data were collected purposively by using Medical Outcomes short form SF-36 invented by RAND corporation, UK for measuring health-related quality of life among Bangladeshi patients where data were expressed as a score on a 0-100 scale. Data analysis was done by using software SPSS version 19. Results: A total of 105 cases were selected purposively amongst which majority were in the age group of 50-60 years with mean age of 55.27 years. Among the respondents 97.1% were males and 98.1% were Muslims. Majority (41%) of them were retired personnel. The mean monthly income was Tk. 16,393.56. Regarding education level 73% of the study population were SSC pass and below. Among the study group, 27(25.7%) patient had undergone coronary artery bypass graft operation. The study group possessed a total quality of life obtaining 63.4% score in their interviews as per SF-36. Among the whole study group, mental components score (63.61%) was found slightly higher than physical components score (63.2%). CABG operated patients mental component score (69.43%) was found relatively higher than Non CABG patients mental component score (60.01%). Patients having better monthly income as well as better educational level possess better mental component and total quality of life than others. Conclusion: It is of paramount importance to maintain the quality of life among coronary heart disease patients. Mental assurance and surgical intervention can improve quality of life among coronary heart disease patients. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 90-94